Managing reindeer lichen during forest regeneration procedures: Linking Sami herders' knowledge and forestry - Roturier, Samuel (HAL CCSD, 2009)
In northern Sweden, conventional forest regeneration procedures applied in modern commercial forestry can disturb terricolous lichen (Cladina spp.) pastures. This has become a source of conflicts with Sámi reindeer herders. The overall aim of this thesis was to investigate forest regeneration strategies that may minimise the disturbance to, and promote the regeneration of, reindeer lichen pastures. The Sámi herders' practices and knowledge related to the lichen resources were also analysed. Effects of gentle soil preparation methods on the re-establishment of lichen cover, reindeer grazing and establishment of Pinus sylvestris planted seedlings were studied in a field experiment. Using the HuMinMix-technique to mix the lichen mat with humus and mineral soil (humix-substrate), was found to promote lichen mat recovery more effectively than conventional scarification. Seedling establishment was highest for mounding and tracks with mineral soil. Rates of seedlings mechanically damaged, possibly caused by reindeer trampling in winter, indicates that planting on densely grazed areas should be avoided to minimize sources of conflict and to prefer either direct seeding or natural regeneration instead. According to a survey, complete re-establishment of the lichen mat after soil preparation was estimated to take about one decade on humix-substrate, compared to probably more than five decades following conventional harrowing. Possibilities for artificial dispersal of reindeer lichen, e.g. in areas disturbed by conventional soil preparation, were also studied. The substrate was identified as a key factor for lichen establishment. In this regard, mineral soil was identified as a poor substrate for reindeer lichen immobilization, while milled organic materials, such as moss, were suitable substrates for lichen immobilization and growth. All dispersal methods tested resulted in lichen establishment, but transplanted lichen cushions were heavily depleted by reindeer grazing, while fragmented lichen thalli were much less ...